Hak-Hak Perempuanterhadap Harta Dalam Suku Karo (Memaknai Simbol dalam Rangka Perubahan Hukum di Masyarakat) - Rasta Pinem (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
Indonesia is a legal state that guarantees the rights of every citizen equally, meaning that everyone has the same rights. Even the 1945 Constitution as the Indonesian constitution regulates the existence of human rights and Indonesian citizens' rights clearly and fairly. But Indonesia is also a country with a large number of tribes. Therefore the culture of each tribe in Indonesia can be different. Talking about the rights of citizens, it does not escape the right to inheritance. Property rights to women in karo tribes are considered unfair compared to the rights to property owned by men in karo tribes.